Silent communications - embodied between the lines : a study describing nonverbal behaviour patterns within the South African multicultural HIV treatment context. - Smith, Samantha Meghan Coralie (My University, 2009)
This dissertation aimed to describe nonverbal behaviours in South African multicultural HIV treatment contexts. It also aimed to identify the most appropriate method for nonverbal behaviour data analysis and transcription. The study used a single-case, parallel design, which incorporated three qualitative methodological tools; ethnography, a modified form of conversational analysis and interviews. Data used was from a preexisting videotaped database, belonging to a larger research project. Data consisted of 4 videotaped interactions between doctors and caregivers of children with HIV/Aids at the Red Cross Children’s Hospital. Through the use of polyphonic transcription, five nonverbal domains - eye gaze, body posture, facial expression, gesture and head posture – were analysed. Patterns and trends of these transcripts were crosschecked with data from the existing set as well as with data and findings from this and other research sites. Findings identified correlations between nonverbal behaviour patterns, interpersonal dynamics and communicative transfer. Specific critical moments of collaboration between caregiver and practitioner as well as nonverbal behaviour roles in communicative and interactional dynamics were also identified. Study findings thus posses the potential to; facilitate effective medical interactions, direct future nonverbal behaviour research and guide the development of medical education and policy.
Keywords: Nonverbal behaviour; Children with HIV; HIV treatment; Silent conversations